The Influence of Product Diversity and Product Quality on Purchasing Decisions at Miniso Resinda Park Mall Karawang: Manajemen Pemasaran - Mila Sari Nurasyiah; Citra Savitri; Syifa Pramudita Faddila (Primanomics : Jurnal Ekonomi & Bisnis, 2024)
Miniso is a retailer that is popular among customers in the highly competitive retail sector. Miniso is a favorite retailer among consumers, but in the era of globalization, product diversity and product quality have become the main factors in consumer purchasing decisions. Miniso is a brand from China that produces and sells various kinds of fashion goods and daily equipment. This brand offers unique products such as accessories, fashion equipment, modern household goods, and modern electronic products. One of the main variables that influences customer purchasing decisions is the phenomenon of decreasing competition in product diversity and product quality. The aim of this research is to understand whether product diversity and quality influence consumers' decisions to buy Miniso accessories and the results of this research are expected to help Miniso develop, especially in the accessories product category, so that it can outperform its competitors. By using the Partial Least Square-Structural Equaral Model (PLS-SEM) approach and the SmartPLS 3 analysis tool, this research uses quantitative methods. The research population was 5,250 people, with a total sample of 372 respondents who had previously purchased Miniso products, selected through Accidental Sampling. The research results show that there is a significant positive correlation between product diversity, product quality, and purchasing decisions for Miniso Resinda Park Mall products. For future researchers, it is recommended to add additional variables such as price, digital marketing, or content marketing strategies related to Miniso.